Clinical presentation, outcomes and factors associated with mortality: A prospective study from three COVID-19 referral care centres in West Africa. (July 2021) - Jaspard, Marie; Sow, Mamadou Saliou; Juchet, Sylvain; Dienderé, Eric; Serra, Beatrice; Kojan, Richard; Sivahera, Billy; Martin, Caroline; Kinda, Moumouni; Lang, Hans-Joerg; Bangaly Sako, Fodé; Amara Traoré, Fodé; et al.
Highlights: Few data are available regarding the clinical presentation of COVID-19 in Africa. Almost one-third of patients hospitalised for COVID-19 show clinical worsening. SARS-CoV2 mortality is 5% in West Africa, a result similar to Europe. Factors associated with mortality are age, male gender and high blood pressure. Diabetes is associated with clinical worsening in COVID-19 patients. Abstract: Objectives: The overall death toll from COVID-19 in Africa is reported to be low but there is little individual-level evidence on the severity of the disease. This study examined the clinical spectrum and outcome of patients monitored in COVID-19 care centres (CCCs) in two West-African countries. Methods: Burkina Faso and Guinea set up referral CCCs to hospitalise all symptomatic SARS-CoV-2 carriers, regardless of the severity of their symptoms. Data collected from hospitalised patients by November 2020 are presented. Result: A total of 1, 805 patients (64% men, median age 41 years) were admitted with COVID-19. Symptoms lasted for a median of 7 days (IQR 4–11). During hospitalisation, 443 (25%) had a SpO2 < 94% at least once, 237 (13%) received oxygen and 266 (15%) took corticosteroids. Mortality was 5% overall, and 1%, 5% and 14% in patients aged <40, 40–59 and ≥60 years, respectively. In multivariable analysis, the risk of death was higher in men (aOR 2.0, 95% CI 1.1; 3.6), people aged ≥60 years (aOR 2.9, 95% CI 1.7; 4.8) and those with chronic hypertension (aOR 2.1, 95% CI 1.2; 3.4). Conclusion: COVID-19 is as severe in Africa as elsewhere, and there must be more vigilance for common risk factors such as older age and hypertension.